2009
DOI: 10.1007/s11627-008-9181-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro germination and micropropagation of Givotia rottleriformis Griff.

Abstract: The propagation of Givotia rottleriformis Griff. is difficult as a result of long seed dormancy associated with poor seed germination. The present study was undertaken to develop a protocol to overcome seed dormancy by culture of zygotic embryo axes and then develop an efficient method for micropropagation of Givotia. Best germination frequency (78.3%) was achieved from mature zygotic embryo axes isolated from acidscarified fresh seeds when cultured on Murashige and Skoog (MS) medium (half-strength major salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Moreover, 0 and ½ MS media produced the higher seed germination percentage of Moringa oleifera, compared to full MS medium (Lédo et al 2008). Likewise, Samuel et al (2009) showed that reduction of MS salts to half-strength is sufficient to improve the germination percentage of Givotia rottleriformis, compared to quarterand full-strength. Germination of seeds in media lacking nutritional salts and sucrose might occur because embryos were autotrophic and eliminate the supplemental energy source (Martendal et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 0 and ½ MS media produced the higher seed germination percentage of Moringa oleifera, compared to full MS medium (Lédo et al 2008). Likewise, Samuel et al (2009) showed that reduction of MS salts to half-strength is sufficient to improve the germination percentage of Givotia rottleriformis, compared to quarterand full-strength. Germination of seeds in media lacking nutritional salts and sucrose might occur because embryos were autotrophic and eliminate the supplemental energy source (Martendal et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Germination frequency of Prunus armeniaca seeds reached 100% when cultivated on MS medium supplemented with 1.0 mg L -1 BA (Nathiya et al 2013). Samuel et al (2009) suggested that supplementing the medium with Kin is essential to achieve efficient plant conversion from embryo of Givotia rottleriformis. Seeds of Prunus armeniaca produced the highest mean shoot length in MS medium supplemented with BA (Nathiya et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Under natural conditions, the transit of seeds through intestines of wild animals and birds breaks the tegument dormancy and favors the imbibitions phenomenon, resulting in the rapid and homogeneous germination of seeds (Ishii and Kambou, 2007). However, in vitro seed germination can be favored by various treatments like acid treatment (Samuel et al, 2009;Sambe et al, 2010), cold and hot water treatment (Thokozani et al, 2011), hormonal treatment (Maridass and Thangavel, 2008), breaking the hard seed coat etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, conversely to the present findings, Pickens et al (2003) found that there was no effect of sucrose on seed germination or seedling growth in Tillandsia eizii. Supplying of phytohormones to the medium favors in vitro seed germination (Miller et al, 1992;Maridass and Thangavel, 2008;Samuel et al, 2009). Addition of GA 3 and activated charcoal to the medium enhanced the seed germination and favored the production of healthy seedlings in D. roxburghii.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of GA 3 in the promotion of germination cannot be excluded, since a higher concentration of endogenous GA 3 was observed in seeds that were ready to germinate than in those that were not ready to germinate (CHEN; CHIEN, 2008). In Givotia rottleriformis Griff., a commercially valuable tree belonging to the family Euphorbiaceae, the highest germination frequency (78.3%) was achieved from mature zygotic embryo axes isolated from acid-scarified fresh seeds cultured on Murashige and Skoog (MS) (1962) medium (half-strength major salts) with 28.9 μM GA 3 (SAMUEL et al, 2009). …”
Section: Introductionmentioning
confidence: 99%